Role of BUMDes in Community-Based River Tourism Management - Rizal, Ahmad; Rodiyah, Isnaini (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Village-Owned Enterprises (BUMDes) are strategic instruments for strengthening rural economies through community-based tourism management. Specific Background: In Tambakcemandi Village, the BUMDes-managed river tourism and Café Kalitikung represent local initiatives to utilize natural resources for economic development, yet face managerial, human resource, and funding challenges. Knowledge Gap: Empirical studies that comprehensively explain the concrete roles of BUMDes administrators in managing village tourism using role-based theoretical perspectives remain limited. Aim: This study aims to analyze the roles of BUMDes administrators in managing river tourism and Café Kalitikung in Tambakcemandi Village. Results: Using a qualitative descriptive approach, the findings show that BUMDes administrators perform three main roles: facilitator through provision of tourism infrastructure, mobilisator by engaging local resources and promoting environmental awareness, and regulator by establishing operational policies and environmental management rules. Novelty: This study offers a role-based analytical framework grounded in Edy Suhardono’s theory to explain village tourism governance at the operational level. Implications: The findings provide practical insights for village governments and BUMDes in strengthening sustainable, community-driven tourism management models.